Officer attitudes toward citizen review and professional accountability. (June 2017) - Lee, Heeuk D; Collins, Peter A; Hsieh, Ming-Li; Boateng, Francis D; Brody, David
The practice of citizen review has developed as one method for improving the accountability of law enforcement officers to the general public and to their respective criminal justice organizations. However, little information is available regarding officers' general perceptions of the citizen review process, as well as the perceptions of those officers who have actually been subject to formal review. This study provides analysis of data collected via a survey of commissioned officers in a large metropolitan police department in the Pacific Northwest. Their attitudes and perceptions of their professional and civilian oversight board, the Offices of Professional Accountability (OPA), were measured, and this study found that police officers with a deeper understating of the OPA system were more willing to report misconduct. Also, police officers who possess higher satisfaction attitudes toward the OPA were more likely to report grievances to it.